PENGEMBANGAN MODEL PEMBELAJARAN TERBUKA BERBASIS LITERASI INFORMASI DALAM PEMBELAJARAN MENULIS KARYA ILMIAH MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA DI PERGURUAN TINGGI - Ninit Alfianika, - (2021)
ABSTRACT This study is established to produce learning model based on information literacy in scientific paper writing learning. This study belongs to research and development. 4D (four-D model) has been used as the model within this study, for instance: (1) definition, (2) design, (3) development, and (4) dissemination. This study was conducted at three universities in Padang. The technique of data collection was by following steps in 4D development model (i.e., definition, design, development, & dissemination). The finding of the study revealed some notable things, as follows: (1) Students of Indonesian literature and language education need teaching materials, learning model, and learning evaluation. Teaching materials that are needed by the students concerning with the systematic of writing scientific article; examples related to scientific articles from the result of research; learning model that is needed for students, namely: learning model in which it can give a fun learning; learning model in which it can provide the students' freedom; learning model in which it can improve students' imagination and creativity; direct practices in learning; directions and guidance immediately. Furthermore, direct evaluation which it is done together in the learning process is considered as the evaluation that is match with students' need. (2) The design of open learning model based on information literacy in scientific paper writing learning produced hypothetic model and manual model. (3) There are three stages related to the development process of open learning model which based on literacy information within scientific paper writing learning, for example: validation test, the first stage trial, and the second stage trial. Validation test pinpointed the development of learning model is highly valid and can be tested in the field. Additionally, the first stage trial pointed out students' learning result in scientific writing after used the design of open learning model based on information literacy has average namely 81,25 and it can be classified into good. Further, the second stage trial found out students' learning result in scientific paper writing after used this model has average namely 88,95 and it can be classified into excellent. (4) The main finding within this study was the final model of learning, i.e., open learning model based on information literacy that was considered as suitable model to be used in learning of scientific paper writing. The model has six stages, namely: presenting problems, finding, presenting opinions, conducting guidance, searching the truth, and presenting which shortened into 6 M. Thus, it can be concluded that the result of open learning model based on information literacy contributed to help tertiary students in scientific paper writing learning. The implications of the results within this present study as follows: (1) The open learning model based on information literacy can not only be used in learning to write scientific papers, but can also be used in learning that requires freedom of thought, discovering concepts by yourself, and requires intensive guidance. (2) The open learning model based on information literacy can foster creative thinking and a sense of responsibility among students. (3) Information literacy-based open learning model is supported by technological advances. (4) Information literacy-based open learning model can foster students' reading habits.